Cucina amore. - Brown, Peter (Television director); Rylko, Chris (Film Ideas, 2006)
This popular cooking series features everyone's favorite Italian Chef, Nick Stellino. The series featured nationally on PBS includes all the style, stories, and of course great dishes that Nick creates, making this delectable presentation a cook's delight. Garlic, mint and rosemary marinated lamb chops served with pesto sauce and a hearty grilled mushroom salad. Printable ingredients list included.